2016
DOI: 10.1080/08958378.2016.1179372
|View full text |Cite
|
Sign up to set email alerts
|

Deleterious effects of incense smoke exposure on kidney function and architecture in male albino rats

Abstract: Long-term exposure to incense smoke may have deleterious effects on kidney function and architecture. Though, inhalation is the rout of exposure, findings of this study underscore that incense smoke may also have an effect on non-pulmonary tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 62 publications
0
21
0
Order By: Relevance
“…Previous studies have reported that a wide range of air pollutants including ultrafine particles, PM, and volatile organic compounds produced from incense burning are detrimental to the vascular health 35 . Studies have demonstrated the capacity of incense smoke to induce oxidative stress and inflammation [36][37][38][39] , which may lead to significantly reduced vascular nitric oxide levels and increased levels of endothelin-1 and inflammatory mediators, such as granulocyte-macrophage-colony stimulating factor. The unregulated levels of these mediators would destruct the vascular vasodilation and constriction 40,41 , thereby promoting vascular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that a wide range of air pollutants including ultrafine particles, PM, and volatile organic compounds produced from incense burning are detrimental to the vascular health 35 . Studies have demonstrated the capacity of incense smoke to induce oxidative stress and inflammation [36][37][38][39] , which may lead to significantly reduced vascular nitric oxide levels and increased levels of endothelin-1 and inflammatory mediators, such as granulocyte-macrophage-colony stimulating factor. The unregulated levels of these mediators would destruct the vascular vasodilation and constriction 40,41 , thereby promoting vascular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…We selected the potential confounders based on prior consideration of the associations with risk of ESRD in this population [23][24][25][26]. Experimental studies in animal models suggest that long-term incense use may have deleterious effects on kidney function [27], while the use of Chinese herbal medicine and the risk of ESRD has been described in human studies [28], Conversely, ginseng may have important bioactive constituents that can control pathological conditions associated with diabetic nephropathy [29]. Since information on incense use and intake of ginseng and medicinal soup was available in this population, we had also included these as covariates in the model.…”
Section: Discussionmentioning
confidence: 99%
“…A significant reversal of oxidative stresswas observed within 30 days of cessation of incense smoke exposure, with consequential up-regulation of endothelial function and inflammation, thus confirming that incense smoke may be responsible for the induction of the pathology (37) . Furthermore, the induction of Cytochromes P450 (CYPs) by BaP or other constituents either alone or in combination in rats exposed to incense smoke, maybe responsible for the mechanistic event for the increase in oxidative stress and inflammation of kidney dysfunction and tissue degeneration (19) . Additionally, myocardial degeneration together with increased oxidative stress and inflammation may contribute to the increased risk of cardiovascular and endothelial dysfunction, as well as irregularity in heart rate amongst incense-smoke exposed subjects (43) .…”
Section: Inflammationmentioning
confidence: 99%
“…Several studies demonstrate that continuous exposure to incense smoke predisposes the development of asthma, dermatitis, respiratory complications and hypertension (15)(16)(17) . Moreover, exposure to carcinogens emitted from incense burning increases the risk of cancer development (18)(19)(20) . Furthermore, the pathological and pharmacological effect of incense smoke on organs have been reported in the lung, testis, skin, liver and kidney (19,(21)(22)(23) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation